Epidemiology of heart failure: Study of Heart failure in the Australian Primary carE setting (SHAPE). (9th September 2020) - Liew, Danny; Audehm, Ralph G.; Haikerwal, Deepak; Piazza, Peter; Neville, A. Munro; Lim, Kevin; Parsons, Richard W.; Sindone, Andrew P.
Abstract: Aims: At present, there is no robust information on the prevalence and incidence of heart failure (HF) in the general Australian community. The present study of primary care data sought to estimate the prevalence and incidence of HF in the community and to describe the demographic and clinical profile of Australians with HF. Methods and results: We undertook a retrospective cohort study based on analysis of anonymized medical records of adult patients cared for at 43 Australian general practices between 1 July 2013 and 30 June 2018. Data were extracted from coded and uncoded fields in electronic medical records. The prevalence and annual incidence of HF were calculated, along with 95% confidence intervals, using the 'active' population of people who were regular attenders at the practices. Age‐standardized estimates were also derived using the 2017 Australian population as reference. The mean age of the population with HF was 69.8 years, 50.6% were female, and mean body mass index was 31.2 kg/m 2 . The age‐standardized prevalence was 2.199% [95% confidence interval (CI): 2.168–2.23%], and the age‐standardized annual incidence was 0.348% (95% CI: 0.342–0.354%). These estimates accord with almost 420 000 people living with HF in Australia in 2017, and >66 000 new cases of HF occurring that year. Only 18.9% of patients with definite HF had this formally captured as a 'diagnosis' in their medical record. HF was more frequent among those of lower socio‐economic status. Conclusions: HF is common in Australia. The majority of HF patients do not have this diagnosis optimally noted in their primary care medical records.